Property, wealth, and social change: Piketty as a social science engineer - Savage, Michael; Waitkus, Nora (The British journal of sociology, 2021)
This paper applauds the vision and originality of Piketty's Capital and Ideology. We draw attention to the distinctive methodological perspective which he adopts, which we liken to call “social science engineering.” This allows a problem oriented perspective on long-term global social change which sidesteps siloed disciplinary debates in social science and history about the meaning of modernity, the rise of capitalism, the formation of social groups, and the primacy of nations. We bring out how his theory of property permits him to take forward his overarching insight that economic growth leads to wealth accumulation. This, therefore, challenges long standing sociological perspectives by insisting that modernity is a conservative, rather than a revolutionary and transformative process. We build on this essential contribution by noting some areas where his work can push forward even further, notably that his focus on shifting relativities obscures qualitative historical changes, and more particularly means his analysis of the 20th century is not as provocative as that of the 19th century.
Gesehen am 16.05.2025